(untitled) (Journal of Economic Research & Business Administration, 2024)
The business and investment environments have changed due to the incorporation of ESG concepts into risk management and innovation activities. ESG considerations were first used to address social and environmental issues, but they have since developed into important elements of risk reduction and business strategy. Innovative ESG risk assessment techniques that promote company resilience, sustainable economic growth, and the development of green economies are the focus of this study. To promote sustainable growth and industrial strength, the study focuses on integrating ESG criteria with risk management frameworks, evaluating the effects of ESG on particular sectors, and developing methods for coordinating ESG practices with «green economy» goals. The research takes a multidisciplinary approach, analyzing financial and operational outcomes across industries using both quantitative and qualitative methodologies. The results show that integrating ESG improves financial performance while also encouraging innovation and fortifying risk management systems. Notably, ESG practices increase resilience in times of economic turbulence, lower systemic risks in financial markets, and boost liquidity. Additionally, ESG-driven initiatives, employee productivity, and sustainable growth are found to be positively correlated, especially in industries like banking and manufacturing. Emerging nations like Kazakhstan are coordinating green economy projects with ESG goals despite regulatory obstacles, indicating a worldwide trend toward sustainable practices. This study adds to the expanding corpus of research on the function of ESG in fostering sustainable economic practices and robust markets. Its practical relevance comes from its capacity to direct investors, businesses, and politicians toward the adoption of ESG-driven policies to create a strong and sustainable economic future. Key words: financial resilience, sustainable development, risk management, financial performance, ESG integration.